A cascaded control structure for air-path control of diesel engines. (June 2014) - Zentner, Stephan; Schäfer, Erika; Fast, Gerald; Onder, Christopher H; Guzzella, Lino
In order to comply with increasingly stringent diesel-engine emission legislation, fast and precise control of the turbochargers and exhaust-gas recirculation are necessary. The difficulties lie in certain disadvantageous plant properties such as cross-couplings and non-linearities, the disturbance of the air path by fast operating-point changes and the multitude of air-path configurations that are available. In this paper, a novel model-based approach for air-path control based on cascaded control is proposed. The resulting multi-variable controller has a low sensitivity to the non-linearity of the plant and the disturbances caused by sudden changes in the operating point. Furthermore, the controller is applicable to various types of air-path configuration. This flexibility is demonstrated by a system analysis of the models of two engines which span a broad range of air-path configurations. The performance of the proposed controller is compared experimentally with that of a conventional model-based multi-variable controller, by implementing both on an engine test bench. This comparison confirms that the cascaded controller presented herein can handle the cross-couplings of the system and that it exhibits a lower sensitivity to the non-linearity and the disturbances than the conventional controller does.